Phylogeographic Aspects of Bat Lyssaviruses in Europe: A Review - Dundarova, Heliana; Ivanova-Aleksandrova, Nadya; Bednarikova, Sarka; Georgieva, Irina; Kirov, Krasimir; Miteva, Kalina; Neov, Boyko; Ostoich, Peter; Pikula, Jiri; Zukal, Jan; Hristov, Peter (Pathogens (Basel, Switzerland), 2023)
During the last few decades, bat lyssaviruses have become the topic of intensive molecular and epidemiological investigations. Since ancient times, rhabdoviruses have caused fatal encephalitis in humans which has led to research into effective strategies for their eradication. Modelling of potential future cross-species virus transmissions forms a substantial component of the recent infection biology of rabies. In this article, we summarise the available data on the phylogeography of both bats and lyssaviruses in Europe and the adjacent reg ions, especially in the contact zone between the Palearctic and Ethiopian realms. Within these zones, three bat families are present with high potential for cross-species transmission and the spread of lyssaviruses in Phylogroup II to Europe (part of the western Palearctic). The lack of effective therapies for rabies viruses in Phylogroup II and the most divergent lyssaviruses generates impetus for additional phylogenetic and virological research within this geographical region.
Keywords: evolution; health; transition routes; Chiroptera; lyssavirus phylogroups